![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
1个回答
展开全部
设f(x)=(x-1)^4 *(x+2)^5
则:f(x)=a0 + a1*x + a2*x^2 + ... +a9*x^9
f(1)=a0 + a1 +a2 + a3+... +a9
f(-1)=a0 -a1 + a2 -a3+...+a8-a9
所以:f(1)-f(-1)=2(a1+a3+a5+a7+a9)
a1+a3+a5+a7+a9=(1/2)[f(1)-f(-1)]=(1/2)[0-(-2)^4 *(-1+2)^5]= -8
则:f(x)=a0 + a1*x + a2*x^2 + ... +a9*x^9
f(1)=a0 + a1 +a2 + a3+... +a9
f(-1)=a0 -a1 + a2 -a3+...+a8-a9
所以:f(1)-f(-1)=2(a1+a3+a5+a7+a9)
a1+a3+a5+a7+a9=(1/2)[f(1)-f(-1)]=(1/2)[0-(-2)^4 *(-1+2)^5]= -8
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询